2019
DOI: 10.1007/s11060-019-03104-3
|View full text |Cite|
|
Sign up to set email alerts
|

Incidental intracranial meningiomas: a systematic review and meta-analysis of prognostic factors and outcomes

Abstract: Background Incidental discovery accounts for 30% of newly-diagnosed intracranial meningiomas. There is no consensus on their optimal management. This review aimed to evaluate the outcomes of different management strategies for these tumors. Methods Using established systematic review methods, six databases were scanned up to September 2017. Pooled event proportions were estimated using a random effects model. Meta-regression of prognostic factors was performed using ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
88
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(98 citation statements)
references
References 39 publications
6
88
1
2
Order By: Relevance
“…This finding corroborates a recently published Swedish registry-based study where a difference in waiting times was noted [3]. In the literature, the waiting time from diagnosis to intervention for asymptomatic meningiomas range from 7.3 to 48.8 months [3,7,9].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This finding corroborates a recently published Swedish registry-based study where a difference in waiting times was noted [3]. In the literature, the waiting time from diagnosis to intervention for asymptomatic meningiomas range from 7.3 to 48.8 months [3,7,9].…”
Section: Discussionsupporting
confidence: 90%
“…Histopathological grading often shows WHO grade I or II meningioma, but in our series, we found one anaplastic meningioma of WHO grade III. This has previously been reported in the literature, and the review by Islim et al [7] presents that 3 out of 316 (0.95%) patients had a grade III meningioma. Hence, anaplastic meningiomas are very rare among asymptomatic meningiomas but still sometimes seen.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The rate of sympP in asymptomatic meningiomas was difficult to define from previous studies. In their review, Islim et al 34) described that 66 out of 608 patients with an incidental meningioma developed symptoms during the mean follow-up of about 40 months; this incidence is higher than our result (4.7%; 46 of 989 patients, mean followup of 53 months). This difference is considered to be due to the different inclusion criteria.…”
Section: Symptomatic Progressioncontrasting
confidence: 79%
“…We could not analyze radiological factors in forest plots because few studies assessed their relationships and each study included only a small number of patients with symptom development. Although Islim et al 34) presented radiological factors in their forest plots (online resource 6), raw data were not provided in the original papers. 12,22,27) Analyses of individual data showed that maleness (P <0.0001) and initial volume (median 2.55 vs. 9.96 cm 3 ; P = 0.0032) or initial diameter (median 1.86 vs. 2.67 cm; P = 0.0035), but not age (P = 0.091), were related to sympP (Table 4).…”
Section: Factors Related To Symptomatic Progressionmentioning
confidence: 99%